Experimental Investigation of Solid Fuel Combustion Process in a Hybrid Porous Reactor - Jovicic, Vojislav; Fedorova, Nataliia; Zbogar-Rasic, Ana; Toledo Torres, Mario; Delgado, Antonio (Journal of Energy and Power Engineering, 2017)
One of the most significant human-made methane emission sources is the MSW (municipal solid waste), deposited on sanitary landfills and open dumps. Within this work, an alternative MSW treatment concept is presented, which could provide a relatively clean waste/biomass-to-energy transformation. The proposed procedure comprises of a combustion and a gasification (or pyrolysis) step, which are consecutively taking place in a two-stage hybrid porous reactor system. The core of the system is two packed bed reactors, in which solid fuel (waste or biomass) is mixed with inert ceramic particles of similar size. This paper overviews the initial experimental investigation of the combustion step of a hybrid mixture, composed of wood pellets (fuel) and alumina balls (inert ceramic particles) in a 250 mm-high batch reactor. The temperature profile along the reactor, the concentration of CO and the flame front propagation velocity were measured as a function of the ceramic particle size (11 and 20 mm), the inert-to-fuel mass ratio (0:1, 2:1, 3:1) and the airflow rate (30, 42, 60 l/min). Experiments indicate that an increase of the mass ratio of inert-to-fuel material and a decrease of the inert ceramic particles size lead to a decrease of the maximum temperature of the packed hybrid bed. Measured CO concentrations showed strong dependence on the inert ceramic particle size, i.e. the particle size reduction from 20 to 11 mm resulted in a significant reduction of CO-emission peaks. The maximum flame front propagation velocity of 0.2 mm/sec was detected for the airflow of 42 l/min, the particle size of 20 mm and the mass ratio of 3:1.
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.experi_8
Keywords: Combustion; allothermal gasification; MSW; hybrid filtration combustion; packed bed